Development of an Assertive Training Module to Prevent Bullying on Islamic Boarding School - Rahmawati, Novi Rosita; Khotimah, Husnul; Chusna, Alin Dewi; Thoriquttyas, Titis (LETIGES, 2025)
This study aims to develop an assertiveness training module to prevent bullying in Islamic boarding schools, addressing the need for culturally relevant interventions. While existing programs offer general social skills training, few are tailored to the unique environment of pondok pesantren. The Research and Development (R&D) method was chosen for this study. This study followed the Borg & Gall development model modified and simplified from ten to seven steps. Data were collected using a validation questionnaire assessed by material experts, media experts, and prospective users (Musyrifah). The results of the study showed that the assertive training module was declared feasible in terms of content and media based on validation by media experts (77%) and materials (71%), with a score of the category